Developing circular building components: Between ideal and feasible - van Stijn, Anne (A+BE | Architecture and the Built Environment, 2023)
A building consists of building components, such as a kitchen, façade and roof. By replacing building components with more circular ones during new construction, maintenance and renovation, we can gradually create a circular built environment. In this dissertation, we develop and test 8 circular building components for housing renovation together with Dutch social housing associations and industry partners. Combining ‘Action Research’ and ‘Research through Design’ approaches, we generate knowledge on the development of feasible, circular building components. We present a design tool, assessment model, environmental design guidelines and identify key stakeholder choices. This research makes scientific contributions to circular design theories, management models for the built environment, and research methodology. We recommend 4 changes in practice to implement more circular building components.